Sero-Prevalence of Hepatitis B Virus Infection and Associated Factors Among Pregnant Women Attending Antenatal Care Services in Gedeo Zone, Southern Ethiopia - Tadiwos, Mhiret Belay (J Prim Care Community Health, 2021)
BACKGROUND: Hepatitis B virus infection is a major public health problem worldwide and is a major cause of morbidity and mortality. This study aimed to assess the prevalence of hepatitis B virus infection and associated factors among pregnant mothers in the Gedeo Zone, southern Ethiopia. METHODS: An institution-based cross-sectional study was conducted among 479 pregnant women visiting governmental and private health facilities in the Gedeo zone from January to April 2019. We selected study participants using systematic random sampling techniques. The Eugene strip test was used to determine hepatitis B virus infection among pregnant mothers. We collected the status of HIV of the pregnant women from the records. Other variables were collected from the mothers using interviewer-administered questionnaires. We used binary and multivariable logistic regression for the analysis. An adjusted odds ratios and their 95% confidence intervals (CIs) were calculated to determine the association between HBsAg sero-positivity and various factors. A P-value of less than .05 was considered significant. RESULTS: This study revealed that the prevalence of hepatitis B virus infection among pregnant mothers was 9.2% in Gedeo Zone. A previous history of blood transfusion [AOR = 5.2, 95% CI: 2.1, 12.5], a previous history of hospital admission [AOR = 3, 95% CI: 1.4, 6.6], a history of having an abortion [AOR = 4.1, 95 % CI: 1.5, 11.7], the age of the pregnant women [AOR = 5.1, 95 % CI: 1.5, 18.0], and their HIV status [AOR = 8.1, 95 % CI: 1.9, 36.0] had a statistically significant association with HBsAg sero-positivity. CONCLUSION: Hepatitis B virus infection was found to have higher endemicity (9.2%) in Gedeo Zone which is higher than the national pooled prevalence which was 4.75%. The health facilities must implement early initiation of antenatal care services which incorporate the prevention and control of HBV in the Gedeo Zone.